2014
DOI: 10.1038/ncomms6569
|View full text |Cite
|
Sign up to set email alerts
|

Multiple haplotype-resolved genomes reveal population patterns of gene and protein diplotypes

Abstract: To fully understand human biology and link genotype to phenotype, the phase of DNA variants must be known. Here we present a comprehensive analysis of haplotype-resolved genomes to assess the nature and variation of haplotypes and their pairs, diplotypes, in European population samples. We use a set of 14 haplotype-resolved genomes generated by fosmid clone-based sequencing, complemented and expanded by up to 372 statistically resolved genomes from the 1000 Genomes Project. We find immense diversity of both ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Cis configurations of protein-altering mutations, leaving one form of the gene intact, would be expected to occur more frequently in human genomes to preserve organismal function (Hoehe et al 2014). To test this hypothesis at large scale in 1,092 genomes (Abecasis et al 2012) (Methods), we determined the ratio of cis to trans configurations of protein-altering mutations across all autosomal protein-coding genes for each of the genomes and derived the median of these ratios (Methods; see also Box 1).…”
Section: Global Abundance Of Cis Configurations Of Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cis configurations of protein-altering mutations, leaving one form of the gene intact, would be expected to occur more frequently in human genomes to preserve organismal function (Hoehe et al 2014). To test this hypothesis at large scale in 1,092 genomes (Abecasis et al 2012) (Methods), we determined the ratio of cis to trans configurations of protein-altering mutations across all autosomal protein-coding genes for each of the genomes and derived the median of these ratios (Methods; see also Box 1).…”
Section: Global Abundance Of Cis Configurations Of Mutationsmentioning
confidence: 99%
“…Thus, to fully understand the biology of genes and genomes, the phase of mutations must be known. In a first population level analysis of haplotype-resolved genomes (Hoehe et al 2014), we have shown nonrandom distribution of mutations between homologous gene forms, as indicated by significant abundance of cis configurations with an average cis/trans ratio of approximately 60:40. This raises the question: Could cis-abundance of mutations, the preferential location of mutations on the same chromosomal homologue of an autosomal gene, represent a key characteristic of diploid human genomes?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pure and intact genomic DNA fragments of about 35 Kb are separated in pools for haplotype analysis. For the relatively simple clone pipeline in comparison with BAC clone, fosmid clone was used to operate dilution pools strategy by several groups [33][34][35][36][37][38]. Kitzman et al [33] constructed a single, complex fosmid library in 2011.…”
Section: Fosmid Clone Poolsmentioning
confidence: 99%